Applying a Social Lab Methodology for Adaptation of a Network in Preventing Radicalisation and Polarisation, the Delft Case Study - Abdulla, Jeanne; Nouri, Minale; Bontà, Carlotta; Caruso, Gabriele (Italian Sociological Review, 2025)
This paper presents the relevance of applying a Social Lab Methodology in Adaptation of a Network in Preventing Radicalisation and Polarisation. The research was conducted by Human Security Collective (HSC) as part of the Horizon 2020 Participation project, together with the Strategic Network on Radicalisation and Polarisation (SNRP) in Delft, the Netherlands. Aimed at addressing evolving challenges in radicalisation and polarisation, the research employed a Social Lab methodology because it offers a way to address complex social challenges through involving a diversity of stakeholders (Hassan, 2014). Within the framework of the Delft approach on Preventing and Countering Violent Extremism (P/CVE), the SNRP, formed in 2016 during a national focus on Jihadism, sought to strengthen resilience. Recognising the emerging need to adapt to changing dynamics and shift the focus from crisis response to prevention, the research aimed to answer the question: “What is needed to adapt the SNRP network towards changing times?” To answer this, municipality professionals, religious leaders, civil society organisations, entrepreneurs, and youths participated in the Social Lab during workshops, interviews and discussions. The paper discusses the outcomes from the sessions and presents action points together with concrete recommendations for the Municipality of Delft and the SNRP. Emphasising the importance of adaptable strategies in preventing polarisation and radicalisation, the findings offer insights for policymakers, practitioners and communities navigating dynamic socio-political contexts. Moreover, the paper outlines the Social Lab cycle, the added value of the process, as well as some critical notes on the Social Lab methodology.